Tales of an Ancient Whisperer (2018) - Te, Sahar (Intermédialités / Intermediality, 2019)
In the fall of 2017, I found a series of books with the title Lands and Peoples at the University of Toronto Swap Shop. I went through the illustrations in the books and stared at the images featuring palm trees for longer than I would usually spend on any image.After that, I started to notice the consistent presence of the palm in different contexts. It was “the image” of the date palm that became the centre of my attention and that triggered memories of my personal encounters with the date palm and its fruit.Flashback to my grandfather’s burial and every funeral I have ever been to in Iran…Memories! Not only of my own, but collective memories. I remembered many stories that directly involved dates. There were flashbacks perhaps shaped by my personal memories, those of others, and from the media. I was unable to tell them apart; deep-seeded roots of history.During the winter of 2017, I gathered as much information as I possibly could about the date palm. In early spring of 2018, I bought a box of “Oriental Dates” from an Iranian market in North York, Ontario. I planted the “Oriental Date” seeds and they germinated within three weeks. A month after that, the first seed sprouted. A thousand different possibilities were shaped…